The relationship between vendor managed inventory and operational performance - Kwame Owusu Kwateng; Benjamin Fokuoh; Francis Kamewor Tetteh (Modern Supply Chain Research and Applications, 2022)
Purpose For the supply chain to be responsive in the age of globalization, the firm needs to adopt strategies to enable them to meet the changing market needs. Thus, it is essential to adopt automatic replenishment programmes such as vendor-managed inventory (VMI). This study sought to examine the relationship between VMI and operational performance (OP) and the moderation roles of leadership and digitization in the mining sector. Design/methodology/approach A quantitative approach was used, including primary data collected from industry players in the mining sector in Ghana. A total of 97 industry players were included in the study. Data gathered was analysed using SPSS and LISREL (8.5). Findings The results indicate that VMI significantly affects OP. However, both digitization and leadership failed to moderate the relationship between VMI and OP. Practical implications The study offers mining companies an understanding of VMI applications in their industry. The knowledge will stimulate and improve inventory management practices in the mining industry. Originality/value This study is among the first few attempts to understand VMI in the mining industry, especially in the Sub-Saharan Africa context. It presents a detailed understanding of VMI and opportunities for future research.
Keywords: 650; Digitization; Leadership; Mining industry; Operational performance; Structural equation modelling; Vendor managed inventory (VMI)